Frying sweet potatoes and bananas (saba) in hiller oil its effects on the oil and the fried products - Yuson, Sonia S. (Quezon City University of the Philippines, 1958)
The study examined the effect on the taste of sweet potatoes and bananas when fried in Hiller oil. Samples of oils and fried products were set aside at intervals of two hours during the twenty-hour frying period. The changes in the flavor of the food samples were followed by a panel of nine judges. The study made on the oil included an evaluation of its odor, color, sedimentation and free fatty acid values. After using the oil for 20 hours, the foods fried in Hiller oil were compared with those fried in commercial oil. Samples fried in fresh commercial oil served as the standards.
Keywords: Cookery (Sweet potatoes).